Estructura de las comunidades de peces de las bahías del parque nacional Huatulco, con énfasis en los sistemas de arrecifes de coral - Juárez Hernández, Luis Gibran (Universidad Autónoma Metropolitana, 2014)
The composition and structure were determined of the fish communities in the Bays of Huatulco in Oaxaca, Mexico and their relationship with habitat characteristics (roughness, substratum diversity, type and proportion of substratum, depth). The ichthyofauna was characterized using visual census and longitudinal transects of 10 meters. Six field surveys were performed between January 2009 and December 2010, with a total of 351 transects. Eighty-eight species were identified, belonging to 66 genres and 37 families. The fish community in the Bays of Huatulco were more similar to those in Panama and Costa Rica. The Pomacentridae, Labridae and Carangidae families were most greatly represented. The species with the most abundance and spatial-temporal frequency of occurrence were Thalassoma lucasanum, Stegastes acapulcoensis and Microspathodon dorsalis, which were therefore considered dominant. Spatial-temporal differences existed in the composition, number of species, abundance, richness and diversity. Spatially, the highest values for these community parameters were found in Maguey, Órgano, La Entrega and Violín. Temporally, differences were related to the oceanographic conditions corresponding to the climatic periods prevalent in the region (dry and rainy seasons). Greater abundance was characteristic of the dry period, resulting in an increase in the numerical representation of resident species (T. lucasanum, S. acapulcoensis, Chromis atrilobata, Prionurus punctatus, M. dorsalis and Abudefduf troschelii) as well as the incidence of cyclical species (Harengula thrissina and Selar crumenophthalmus). Meanwhile, the largest number of species and greatest richness and diversity occurred during the rainy season. The community composition and parameters presented differences within each locality, which were related to the type of substratum. The environment consisting of more than one substratum had a greater number of species and more richness, abundance and diversity. The lowest values for these characteristics corresponded to sandy substratum. The roughness and diversity of the substratum were the habitat attributes with the greatest influence on fish composition, abundance, number of species, richness and diversity. Changes in land use caused disturbances in the coral communities in Maguey and Violín, resulting in significant changes in the fish community in Maguey.; Se determinó la composición y estructura de las comunidades ícticas de Bahías de Huatulco, Oaxaca, México, y su relación con los atributos del hábitat (rugosidad, diversidad de sustrato, tipo y proporción de sustrato, profundidad). La caracterización de la ictiofauna se realizó con la técnica de censos visuales mediante transecto de una longitud de diez metros. Seis salidas de campo fueron efectuadas entre enero del 2009 y diciembre del 2010, realizando un total de 351 transectos. Se identificaron 88 especies pertenecientes a 66 géneros y 37 familias. La comunidad íctica de Bahías de Huatulco presenta una mayor afinidad con las comunidades ícticas de Panamá y Costa Rica. Pomacentridae, Labridae y Carangidae fueron las familias mejor representadas. Las especies que presentaron la mayor abundancia y frecuencia de ocurrencia espaciotemporal fueron Thalassoma lucasanum, Stegastes acapulcoensis y Microspathodon dorsalis, por lo que fueron consideradas como dominantes. La composición, número de especies, abundancia, riqueza y diversidad presentan diferencias espacio-temporales. Espacialmente, los valores máximos de estos parámetros comunitarios fueron característicos de Maguey, Órgano, La Entrega y Violín. Temporalmente, estas diferencias corresponden con las condiciones oceanográficas de las épocas climáticas prevalecientes en la región (sequía y lluvias). La mayor abundancia es característica de la época de sequía, resultado del incremento en la representación numérica de especies residentes (T. lucasanum, S. acapulcoensis, Chromis atrilobata, Prionurus punctatus, M. dorsalis y Abudefduf troschelii) así como la incidencia de especies cíclicas (Harengula thrissina y Selar crumenophthalmus), mientras que el mayor número de especies así como la mayor riqueza y diversidad se presentan en la época de lluvias. Al interior de cada localidad, la composición y parámetros comunitarios presentan diferencias, relacionándose con el tipo de sustrato. Los ambientes integrados por más de un sustrato fueron los que presentaron el mayor número de especies, riqueza, abundancia y diversidad. Los valores mínimos de estos, fueron característicos de los sustratos arenosos. La rugosidad y diversidad del sustrato fueron los atributos del hábitat que mostraron una mayor influencia en la composición, abundancia, número de especies, riqueza, abundancia y diversidad íctica. Cambios en el uso de suelo determinaron eventos de disturbio en las comunidades coralinas de Maguey y Violín, influenciando cambios significativos en la comunidad íctica de Maguey.